Determination of power and weight-and-size parameters of passive components of pulsed converters - Afanasyev, A. M.; EreminаA. V. (Technology and design in electronic equipment, 2013)
The paper presents a method for calculating the loss power and weight of passive elements of pulsed converters (PC) depending on the coefficient of the current ripple in the storage inductor and the frequency of switching. The method allows to optimize power and weight-and-size parameters, as well as the PC modes. The curves obtained using the proposed method are presented. The analysis of these curves allows to determine the conditions for minimum loss power and weight of passive components of PCs.